E-terminology - Alberts, Mariëtta (Lexikos, 2002)
Abstract: This article addresses computer applications in terminology and terminography. Terminologists aim at creating source language terms and target language term equivalents for new concepts and thereby enhancing communication in various subject areas and domains. The worldwide market for terminological products is gradually expanding. There is an ever increasing need for the elaboration of terminologies and the distribution of terminologically relevant information, either in computerized form or in printed form, to provide available terminological data to as many users as possible. This article provides various strategies for different users to access multilingual terminology resources. On-line availability of terminological data can empower South African language practitioners and subject specialists. Matters dealing with terminological management systems form a vital part of this article. Outcomes, advantages, constraints and requirements regarding e-terminology are given.Keywords: COMPUTER APPLICATION, ELECTRONIC TERMINOLOGY, E-TERMINOLOGY, HUMAN?COMPUTER INTERFACE, INFORMATION, KNOWLEDGE, KNOWLEDGEBASED SOCIETY, LANGUAGE BARRIER, MACHINE TRANSLATION, MULTILINGUAL TERM EQUIVALENTS, MULTILINGUAL TERMINOLOGY, TERMINOLOGY APPLICATIONOpsomming: E-terminologie. Hierdie artikel behandel rekenaartoepassings in terminologieen terminografie. Terminoloë stel hul ten doel om brontaalterme en doeltaalekwivalente virnuwe begrippe te skep en daardeur kommunikasie in verskeie vakgebiede en terreine te verbeter.Die wêreldwye mark vir terminologiese produkte brei geleidelik uit. Daar is 'n steeds groter wordendebehoefte aan die uitbouing van terminologieë en die verspreiding van terminologies relevanteinligting, in óf gerekenariseerde óf gedrukte vorm, ten einde die beskikbare terminologieseinligting aan soveel gebruikers moontlik te voorsien. Hierdie artikel bied verskeie strategieë aanverskillende gebruikers om toegang tot meertalige terminologiese bronne te verkry. Intydse beskikbaarheidvan terminologiese inligting kan Suid-Afrikaanse taalpraktisyns en vakkundiges bemagtig.Aangeleenthede wat met terminologiese bestuurstelsels te make het, vorm 'n integrale deel vanhierdie artikel. Uitkomstes, voordele, belemmerings en vereistes betreffende e-terminologie wordaangebied.Sleutelwoorde: ELEKTRONIESE TERMINOLOGIE, E-TERMINOLOGIE, INLIGTING, KENNIS, KENNISGEBASEERDE SAMELEWING, MENS?REKENAARKOPPELVLAK, REKENAARTOEPASSING, MASJIENVERTALING, TAALHINDERNIS, TERMINOLOGIETOEPASSING, VEELTALIGE TERMEKWIVALENTE, VEELTALIGE TERMINOLOGIE